LINGUOCULTURAL CODE OF TIME IN THE UKRAINIAN POETIC DISCOURSE OF THE LATE 20TH – 21ST CENTURIES - Бондаренко, Алла (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
Time is a linguocultural phenomenon which reflects the features of a specific linguistic and conceptual worldview. This article’s relevance stems from the importance of studying the representation of the linguocultural code of time in poetic writing. The verbal contexts containing the idea of time have been drawing attention of scholars in semasiology, cognitive science, linguostylistics, and other linguistic disciplines. The realization of axiological semantics in poetic discourse influenced by social and cultural phenomena requires further study. This article aims at revealing the linguistic and extralinguistic factors of the ways linguocultural code is represented in the poetic discourse of the late 20th –21st centuries. The purpose of the study is to analyze the linguistic and non-linguistic mechanisms of representation of the linguocultural code of time in the plane of poetic discourse of the late XX–XXI centuries. Methods. The reconstruction of the peripheral subsystem of verbal images of time relies on the procedure of field modelling. Component analysis has been used to identify the conceptual operators of evaluations. Distributional analysis has been used in the semantization of temporal vocabulary within the examined images. Semantic and stylistic method has been used to outline the connotation of verbal units within temporal images, as well as to draw image parallels. Contextological analysis has been employed to reveal the verbal and conceptual mechanisms of termporal images’ construction and functioning. In order to examine the non-verbal factors of temporal image construction, contextual-interpretational analysis has been used. Syntaxemic analysis has served to address the syntaxemic roles of nouns of the temporal group. Results. Components of the peripheral subsystem of temporal images have been reconstructed, and their contextual interaction with the sociocultural environment has been outlined. The study has revealed image paradigms which rely on vocabulary of the temporal group. It has also identified conceptual operators and axiological poles of specific evaluations, including the aesthetic, utilitarian, emotive, teleological, and ethical ones produced by metaphors of time. For the first time, the study has offered a reinterpretation of the temporal code in the poetic discourse of the late 19th – 20th centuries. It is based on the idea of the dynamics of axiosemantic processes at the periphery of the functional and semantic field of temporality. Conclusions. Verbal images of time form the peripheral zone of the functional-semantic field of temporality. This can be explained by their relation to the socio-cultural environment, which plays a significant role in the aesthetics of postmodernism associated with the view of fixed values. As a result of the influence of this context, there is an axiological and stylistic reinterpretation of the linguistic and cultural code of time.